Pattern of congenital heart diseases among children with Down syndrome seen in Aminu Kano Teaching Hospital, Kano, Nigeria - Asani, Mustafa; Aliyu, Ibrahim; Also, Umar (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: The association between Down syndrome (DS) and congenital heart disease (CHD) was first recognised by Garrod in 1894. Several studies have reported about 40-60% prevalence of CHD in DS and a predominance of left to right shunts like atrioventricular septal defects (AVSDs), ventricular septal defect, patent ductus arteriosus and atrial septal defect. Objectives: This study was carried out to find out the prevalence and types of CHD among children with DS. Materials and Methods: This was a retrospective study of the echocardiographic data collected over a 24-month period, between October 2009 and September 2011. The echocardiographic diagnosis of all children with DS referred was reviewed. Results: A total of 35 cases of DS were seen. The age ranged from 0.5-30 months. About 60% of the children with DS were aged 6 months and below. There were 19 males and 8 females giving a M: F ratio of about 2:1. A total of 77.1% of the children with DS had CHD. The most common CHD is AVSD (40%), followed by atrial septal defect (22.25%). A total of 22.25% had normal echocardiographic study. Conclusion: Early referral and screening of all babies born with the clinical phenotype of DS should be encouraged due to the high prevalence of CHD.